Determinants Of Profitability In Regional Development Banks: Case Study In 2019 – 2021 - Puspitasari, Devy Mawarnie; Sihite, Heryanto Romario; Napitupulu, Sotarduga (UNIVERSITAS PAKUAN, 2023)
This study aims to analyze financial performance based on profitability disclosures at Regional Development Banks (BPD) in Indonesia. The object of research is the annual financial statements of companies with a population of 27 Regional Development Banks operating in 2019 2021. Determination of the sample using documentation techniques and the number of samples (n) that meet the criteria as many as 81 samples. The research uses a quantitative approach with secondary data sources in the form of annual reports. The data analysis method used is the normality test, classical assumption test, multiple linear regression, hypothesis testing, and coefficient of determination test at a significance level of 5%, the data is processed using the SPSS version 24 application. The statistical test results show the independent variable Capital Adequacy Ratio, Non -Performing Loan, Good Corporate Governance, Institutional Share Ownership, Operating Expenses on Operating Income, and Earnings Management together affect the dependent variable Return on Assets and Return on Equity. The contribution levels of the two regression models are 83.70% and 86.50%. The determinant factors that influence fluctuations in profitability (ROA and ROE) are Capital Adequacy Ratio, Non-performing Loan, Operating Expenses to Operating Income, and Earnings Management.